The development of Single-chain Variable Fragment (ScFv) antibodies against Toxoplasma gondii by phage-display / Sherene Lim Swee Yin - Lim, Sherene Swee Yin (2012)
The obligate intracellular protozoan parasite, Toxoplasma gondii, is the etiologic agent of an opportunistic infection affecting mainly immunocompromised patients, infants and neonates with immature immune system. There is a need for alternative antiparasitic treatment for toxoplasmosis due to the associated toxicity and teratogenicity of the current drug treatment regime. To investigate a potential alternative strategy, we have used the phage-display system and developed a novel biopanning procedure to isolate single-chain Fv (scFv) antibodies probed against tachyzoites – the rapidly replicating form of T. gondii responsible for acute disease. The resulting scFv antibody library (complexity of 1.62 X 104 independent transformants) was co-incubated with the tachyzoites in a solution phase single-round biopanning procedure that was subtracted against a human cell line to minimize false positives. Phage-scFv output clones from the biopanning showed an average of at least 5.6-fold higher binding titer to T. gondii relative to unpanned clones. Here we show that despite well-acknowledged difficulties associated with biopanning with cells, this rapid biopanning approach was able to effectively generate specific scFv against T. gondii. ScFv TG130 which was isolated from this study demonstrated a 5-fold enrichment of binding to its’ intended target T.gondii tachyzoites compared to the negative control cell line WRL68. Statistical assessment of the titer of bound recombinant scFv TG130 phage was found to be significantly higher with T. gondii than with WRL68 (Mann-Whitney test, P = 0.0303, n= 12).In order to improve the binding properties of the anti- T. gondii scFv antibody, a second generation antibody library was generated based on the isolated scFv TG130 by using complementarity-determining region (CDR) mutagenesis for affecting an in vitro antibody affinity maturation. Site-directed randomized mutations were introduced into specific DNA residues within the CDR known as hot spots – which are sequences that are prone to somatic hypermutations during the in vivo affinity maturation of antibodies.A screening strategy with increased stringency to select for antibodies with increased dissociation rate was employed to isolate improved scFv binders. Comparisons between the parental antibody and the affinity-matured antibody clone revealed that there was not a statistically significant difference in the binding titers of both antibodies to the target antigen T. gondii, although average titers for the affinity-matured TP60 was at least 1.8-fold higher than its parental counterpart. However, statistical analysis showed that the matured antibody fragment outperformed the parental antibody in terms of antibody specificity for T. gondii relative to negative control (t-test, P = 0.018, n = 3),indicating improved antibody selectivity for its target. These results demonstrate that scFv antibodies to T. gondii with improved properties can be generated through a combinatorial approach of phage-display and an in vitro antibody affinity maturation procedure. The potential implication of this study is for the enabling of the discovery and evolution of recombinant antibody fragments against T. gondii antigens in its native form and the development of bioimaging and cell-targeting ligands against this parasite.